2018
DOI: 10.1111/1751-7915.13282
|View full text |Cite
|
Sign up to set email alerts
|

Caecal infusion of the short‐chain fatty acid propionate affects the microbiota and expression of inflammatory cytokines in the colon in a fistula pig model

Abstract: SummaryShort‐chain fatty acids (SCFAs), particularly butyrate, are known to suppress inflammation, and regulate the gut bacterial ecology. However, little is known about propionate. We report here that propionate infusion in the caecum dramatically affected the structure of colonic microbiota of pigs based on 16s rRNA high‐throughput sequencing. Sixteen pig models were perfused with saline or sodium propionate by a fistula in the caecum. At d 28, all pigs were slaughtered for analysing bacterial metabolites, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 46 publications
3
43
0
Order By: Relevance
“…IFN-γ is an important immune factor that functions in control of cryptosporidiosis [ 35 ]. Butyrate regulates gut bacterial ecology while propionate upregulates NF-κB and IL-18 [ 36 ]. Butyrate is also a histone deacetylase inhibitor and is involved in cell cycle and cell proliferation [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…IFN-γ is an important immune factor that functions in control of cryptosporidiosis [ 35 ]. Butyrate regulates gut bacterial ecology while propionate upregulates NF-κB and IL-18 [ 36 ]. Butyrate is also a histone deacetylase inhibitor and is involved in cell cycle and cell proliferation [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, SCFAs, particularly butyrate, are known to suppress intestinal inflammation[71, 72] and down-regulate nitric oxide and proinflammatory cytokines in multiple cells or tissues[73, 74]. On the other hand, over-stimulation of SCFAs also up-regulate inflammatory cytokines in the colon of pig[75] and induce ureteritis and hydronephrosis in mice[17]. Increasing evidence indicate that elaborate regulation of SCFA on immune system are dose- and tissue-dependent, and exert di□erent e□ects at key developmental time periods[76].…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between flora and sIgA is significant [ 25 ]. SCFAS are confirmed to be the metabolites of intestinal flora, which also interacts with the gut [ 26 , 27 ]. The changes in viscera index, the expressions of sIgA and SCFAS, and the changes in the pulmonary and intestinal flora in our study indicated that FTF could regulate the flora and mucosal immunity of the lung and intestine.…”
Section: Discussionmentioning
confidence: 99%